Business Angel Investment in Russia: Problems and Prospects - Veselovsky, Mikhail Yakovlevich; Suglobov, Alexander Evgenievich; Khoroshavina, Natalya Sergeevna; Abrashkin, Mikhail Sergeyevich; Stepanov, Alexander Annayarovich (International Journal of Economics and Financial Issues, 2015)
Russian state policy is aimed at the formation of the national innovation system. Stimulation of the innovation activities of entrepreneurs is crucial in terms of innovative development of the country. In many ways, it is determined by the availability of financial resources in the early stages of the innovation project. At the same time, a high level of risk determines the reluctance of traditional investors to make investments at this stage of development of the company. Funding for the seed stage of the innovative project can be often provided by private investors only. In this regard, the role of business angel investments, which are a powerful financial resource for the seed stage of the project, increases. Business angels can provide financial assistance when traditional investors, such as banks and even venture capital funds, refuse. The analysis of statistical information on the development of business angel investing in Russia was carried out to achieve the goal. The article deals with current trends and prospects of development of business angel investing in Russia, defines their role and importance for the development of the Russian economy. Special attention is paid to the problems faced by private investors who wish to finance the early stages of innovative projects. Keywords: business angel investment, venture funding, innovation activity JEL Classifications: O12; O16; O32